2009
DOI: 10.1159/000224873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tadalafil on Renal Resistivity and Pulsatility Index in Partial Ureteral Obstruction

Abstract: Introduction: To investigate the effect of tadalafil on Resistivity Index (RI) and Pulsatility Index (PI) in partial unilateral ureteral obstruction (PUUO). Methods: Twelve New Zealand rabbits were assigned into two groups. Baseline renal Doppler ultrasonography (USG) was performed in all rabbits. The rabbits in group 1 received tadalafil for a month (10 mg/72 h) and group 2 was defined as sham. After 1 month, in both groups left PUUO was created. Renal Doppler USG was performed to measure RI and PI parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Various studies concerning PDE5 inhibitors have reported different effects. These include intracellular NO production inhibiting platelet aggregation (9), improved renal blood flow in a model of partial ureteral obstruction induced in rats (10) and protection against tubular apoptosis (11). …”
Section: Introductionmentioning
confidence: 99%
“…Various studies concerning PDE5 inhibitors have reported different effects. These include intracellular NO production inhibiting platelet aggregation (9), improved renal blood flow in a model of partial ureteral obstruction induced in rats (10) and protection against tubular apoptosis (11). …”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics and results of the human studies evaluating the potential reno-protective effects of PDE5Is are summarized in Table 1 [17,24,38,39]. The main characteristics and results of the animal studies on currently proposed AKI models evaluating the potential reno-protective effects of sildenafil, tadalafil, icariin, vardenafil, zaprinast-udenafil are summarized in Table 2 [23,30,, Table 3 [29,35,45,49,[62][63][64][65][66][67][68][69][70][71][72][73][74], Table 4 [18,75,76], Table 5 [45,77,78], and Table 6 [21,40,79,80], respectively. The main characteristics and results of the animal studies in the AKI-CKD transition spectrum (focusing on renal function and/or structure alterations for up to three months, not fulfilling the KDIGO definition for CKD [6]) evaluating the potential reno-protective effects of sildenafil, tadalafil, icariin, vardenafil, zaprinast-udenafil are summarized in Table A1 [109,110], respectively (Appendix B).…”
Section: Resultsmentioning
confidence: 99%
“…Por anos, os coelhos vêm sendo o modelo experimental de escolha em pesquisas primárias para a avaliação da obstrução ureteral induzida e da insuficiência renal, em virtude da acessibilidade, do porte, da facilidade de manuseio e de manipulação cirúrgica (COLEY et al, 1995;KIM et al, 2004;AYYILDZ et al, 2009;LIMA et al, 2013;KAYA;ÇETİNKAYA, 2022;SU et al, 2022). Frente a isso e à similaridade anatômica com o diâmetro ureteral dos gatos, os coelhos são um modelo ideal para estudos primários com perspectivas para aplicação clínica em felinos.…”
Section: Lista De Ilustraçõesunclassified